Priming cooperation in social dilemma games - Michalis Drouvelis; Robert Metcalfe; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2010)
Research on public goods mainly focuses its attention on the ability of incentives, beliefs and group structure to affect behaviour in social dilemma interactions. This paper investigates the pure effects of a rather subtle mechanism on social preferences in a one-shot linear public good game. Using priming techniques from social psychology, we activate the concept of cooperation and explore the extent to which this intervention brings about changes in people's voluntary contributions to the public good and self-reported emotional responses. Our findings suggest that priming cooperation increases contribution levels, controlling for subjects' gender. Our priming effect is much stronger for females than for males. This difference can be explained by a shift in subjects' beliefs about contributions. We also find a significant impact of priming on mean positive emotional responses.
Keywords: C92; D01; H41; 330; Priming; contributions; beliefs; emotional responses; public goods experiments; Gefangenendilemma; Öffentliches Gut; Spieltheorie; Kooperation; Emotion; Sozialpsychologie